THE ROLE OF LOCAL CULTURE ON THE WORK PRODUCTIVITY - Rini Aristin; Hasbullah Hasbullah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This study explores the role of the local culture Prebhesan 'Lakona Lakoni' in influencing faculty productivity at Universitas Madura. The Prebhesan 'Lakona Lakoni' culture, which emphasizes values such as responsibility, hard work, and camaraderie, is considered a key element in shaping a productive work environment. Employing a qualitative approach with a case study design, this research investigates how these cultural values are integrated into academic practices and their impact on faculty performance. Data were collected through in-depth interviews and observations and analyzed using thematic analysis. The findings indicate that the implementation of Prebhesan and 'Lakona Lakoni' values significantly enhances faculty motivation and engagement and strengthens social interactions within the workplace. However, there is variation in the adoption of cultural values across different faculties, highlighting the need for a more uniform approach. This study provides insights into how local culture can serve as an effective managerial tool for improving work productivity in academic settings. Recommendations for Universitas Madura include the development of more integrated policies to support the implementation of local culture and the alignment of its application across faculties. Further research is needed to explore the application of local culture in other higher education institutions and its impact on various managerial and academic aspects.